Case Report: Synchronous pancreatic sarcomatoid carcinoma and gastric cancer: a case study with literature review - Lu, Genlin; Tu, Jinming; Jiang, Renya (Frontiers in Immunology, 2025)
ObjectiveTo illuminate the pathological characteristics and treatment of synchronous pancreatic sarcomatoid carcinoma(SCP) and gastric cancer using a case report and comprehensive literature review.MethodsClinical presentation, pathological findings and immunohistochemical results of a patient with SCP and gastric cancer were reviewed. A surgical treatment strategy with best supportive care, including nutrition support, was adopted. A comprehensive literature review was conducted.ResultsA 69-year-old female patient presented to the general surgery clinic with ten days of abdominal pain. A Type IIc lesion measuring 30 mm in diameter was found in the gastric angle. Additionally,a thick-walled, solid mass with dimensions of 33 mm by 30 mm was detected in the pancreatic tail. HE staining revealed a moderately to poorly differentiated adenocarcinoma and partial mucinous adenocarcinoma in gastric angle and a sarcomatoid carcinoma with low-grade adenocarcinoma components in pancreatic tail. Immunohistochemical assay of the mass in pancreatic tail showed partial positivity for CK(pan), CK7, CD56, CD138, CEA, EMA, and Ki-67 (60%). The patient’s serum levels of CA199, CEA, CA125, and CA242 were sharply decreased postoperatively but remained above normal limits. However, these markers were predominantly increased in the presence of multiple liver metastases.Malnutrition and progressive disease occurred despite the adoption of EN plus PN and best supportive care, and the patient died on postoperative day 107.ConclusionsSynchronous SCP and gastric cancer are first reported in this study. Surgical treatment remains effective despite an even poorer prognosis.